Microalgal and bacterial auxin biosynthesis: implications for algal biotechnology. (February 2022) - Lin, Hanzhi; Li, Yantao; Hill, Russell T
Graphical abstract: Abstract : Optimization of microalgal growth and high-value metabolite production are key steps in microalgal mass culture for the algae industry. An emerging technology is the use of phytohormones, like indole-3-acetic acid (IAA), to promote microalgal growth. This requires an understanding of the biosynthesis of IAA in microalgae-bacteria associations and its function in regulating algal physiology and metabolite production. We review the current advances in understanding of microalgal and bacterial auxin biosynthesis and their implications for algal biotechnology.